Report of Nocardia species isolated from soil by 16S rRNA gene sequencing method in Isfahan, Iran - samane bourbour (Biological Journal of Microorganism, 2016)
Introduction: The genus Nocardia belongs to aerobic Actinomycetes. They are a large group of soil-dwelling bacteria that are distributed worldwide. Using various key conventional and molecular diagnostic tests, several Nocardia isolates were identified, characterized and distinguished.